Performance of Implementation IBR-DTN and Batman-Adv Routing Protocol in Wireless Mesh Networks - Yuliandoko, Herman; Sukaridhoto, Sritrusta; Al Rasyid, M Udin Harun; Funabiki, Nobuo (EMITTER International Journal of Engineering Technology, 2015)
Wireless mesh networks is a network which has high mobility and flexibility network. In Wireless mesh networks nodes are free to move and able to automatically build a network connection with other nodes. High mobility, heterogeneous condition and intermittent network connectivity cause data packets drop during wireless communication and it becomes a problem in the wireless mesh networks. This condition can happen because wireless mesh networks use connectionless networking type such as IP protocol which it is not tolerant to delay. To solve this condition it is needed a technology to keep data packets when the network is disconnect. Delay tolerant technology is a technology that provides store and forward mechanism and it can prevent packet data dropping during communication. In our research, we proposed a test bed wireless mesh networks implementation by using proactive routing protocol and combining with delay tolerant technology. We used Batman-adv routing protocol and IBR-DTN on our research. We measured some particular performance aspect of networking such as packet loss, delay, and throughput of the network. We identified that delay tolerant could keep packet data from dropping better than current wireless mesh networks in the intermittent network condition. We also proved that IBR-DTN and Batman-adv could run together on the wireless mesh networks. In The experiment throughput test result of IBR-DTN was higher than Current TCP on the LoS (Line of Side) and on environment with obstacle.Keywords: Delay Tolerant, IBR-DTN, Wireless Mesh, Batman-adv,Â Performance